The Fama-French five-factor model and the US-China trade war: An empirical investigation of the Indonesia, US, and China stock market - Elizabeth, Irenna; Sulistiawan, Dedhy; Grigorescu , Adriana (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2022)
Despite numerous studies of the US and China trade war effect being published over the last seven years, this topic has remained equivocal. The portfolio formation model that underlies the arbitrage pricing theory is still relatively small, especially for the portfolio performance of the Fama-French five factors (5FF) model that examines the global economic crisis. Focusing on the trade war year, the study aims to examine the effect of accounting information on portfolio performance by using the 5FF model. This study employs a dummy panel least square regression model, the data are analyzed from Indonesia, US, and China stock markets with 864 portfolio monthly combinations ranging from 2016 to 2019. The result of the study shows that the US-China trade war strengthens the beneficial impact of market risk on portfolio performance in the Indonesian Stock Exchange. On the other hand, the war has no impact on the relationship between market risk and the performance of a portfolio of US stocks. However, it lowered the beneficial impact of size on portfolio performance for both the US and China stock markets. The robust 5FF of accounting information within the study is size and investment. According to the study, systematic risk and idiosyncratic risk should be given more consideration by both investors and companies to prevent unneeded economic losses and manage the risk that could have a greater impact on the stock market.